Mass profiles of galaxy clusters from X-ray analysis - Ettori, Stefano; Donnarumma, Annamaria; Pointecouteau, Etienne; Reiprich, Thomas H.; Giodini, Stefania; Lovisari, Lorenzo; Schmidt, Robert W. (Space science reviews, 2013)
We review the methods adopted to reconstruct the mass profiles in X-ray luminous galaxy clusters. We discuss the limitations and the biases affecting these measurements and how these mass profiles can be used as cosmological proxies.